Beyond Sequencing: What does a risk-based analysis of core institutions, domestic financial and capital account liberalization reveal about systemic risk in Asian Emerging Market Economies? - James H. Chan-Lee (Asian Development Bank Institute (ADBI), 2002)
The proliferation of financial crises provoked by volatile capital flows since the mid- 1990s raises grave concerns. Unfortunately, existing theory is ill adapted to analysing capital account crises, when weak institutions and incomplete domestic financial liberalisation (DFL) interact with significant capital account opening (KAO). A clear distinction between systemic capital vs. classic current account crises is needed. Good core institutions reduce systemic risk; well-staged DFL is also low risk, and both should be established quickly. Pragmatic FX liquidity management, effective prudential supervision and DFL are essential before full-scale KAO. High-risk elements of KAO should be avoided until safeguards are in place, contradicting the big bang approach. Systemic risk is assessed here using Bank for International Settlements (BIS) indicators of external vulnerability and our indicators for core institutions, DFL and KAO. Pragmatic guidelines for the PRC are outlined using a risk-based approach (see also APF Policy Recommendations www.adbi.org/apf_main.html).
hdl:11540/4151
Keywords: 330